In vitro antiviral activity of polygonum minus extracts against herpes simplex virus 1 - Alvin, Paul (2015)
The use of medicinal plants as preventative and curative treatment may be integral when a complete treatment is not yet available. Hence, the purpose of this study was to conduct an evaluation on Polygonum minus extracts over its effect against Herpes Simplex Virus 1 (HSV-1) infection in vitro. Methanol, ethanol and aqueous extracts of P.minus were obtained through evaporation under reduced pressure via rotary evaporator. Cytotoxicity testing of P.minus extracts was conducted on Vero cells using MTT assay. DPPH and Folin-Ciocalteu assay were used to evaluate its radical scavenging activity and phenolic content respectively. To better understand its medicinal properties, an in vitro treatment was carried out by means of time-of-addition tests; simultaneous treatment, pre-treatment and posttreatment. Infection with HSV-1 was performed at MOI of 1 and inoculated with methanol and ethanol extracts at its maximum non-toxic dose concentration of 37.50 µg/ml. In simultaneous and pre-treatment, both extract appeared to exert inadequate effect against HSV-1 infected cells (where cell viability recorded well below 60%). However, in post-treatment test, only aqueous extract showed desirable effect where cell viability is maximally retained. This is despite the fact that aqueous extract displayed the lowest radical scavenging activity (IC50 = 146.58 µg/ml, with maximum inhibition at 8 mg/ml concentration), having the lowest phenolic content (61.68 ± 11.621 mg GAE/l at 8 mg/ml concentration), albeit a higher cytotoxicity (IC50 = 408.03 µg/ml) towards Vero cells compared to methanolic extract. Hence, preliminary finding suggests aqueous P.minus extract has curative potential towards HSV-1 infected cells despite its subpar antioxidant activity. Indeed, further studies are required to make clear the exact curative effect of P.minus towards HSV-1 infection before a more conclusive experimental findings be made.